Some raphignathoid mites (Acariformes: Prostigmata) in Lorestan Province, with re-description of Raphignathus evidus Fan & Yin as a new record from Iran - Parisa Hatami; Shahriar Jafari; Mohammad Ahmad-Hosseini (Persian Journal of Acarology)
Mites of Raphignathoidea are important natural enemies of some small pests like phytophagous mites and some insects in various ecosystems. Fauna of this superfamily was studied in Lorestan province, Iran, during 2019–2020. In this survey, a total of 20 species belonging to seven genera from three families were collected and identified. Among them, Raphignathus evidus Fan is re-described and recorded as new to Iranian mite's fauna.